Slowed rotor wind tunnel testing of an instrumented rotor at high advance ratio - Berry, B.; Chopra, I. (My University, 2014)
Compound helicopter designs utilize a slowed main rotor, which reduces RPM as flight speed increases to maintain sub-critical tip Mach numbers. These concepts are therefore expected to operate at high advance ratios (1–2.5 or higher). There is a need for experimental data sets in this flight regime to validate and devel-op predictive tools. Systematic testing in the Glenn L. Martin Wind Tunnel (University of Maryland) was con-ducted on an instrumented Mach-scale articulated rotor (1.7 m diameter) up to an advance ratio of 1.61. The following measurements were taken: steady and dynamic 6-component hub loads (fixed-frame), shaft torque (rotating frame), root flapping angles, pitch link loads, blade torsion and flap bending moments at 5 spanwise stations, and 16 chordwise blade pressures at 30% radius spanwise location. The selected results detailed in this paper revealed insights into high advance ratio, reverse flow phenomenon such as reverse chord dy-namic stall and the resulting impact on loads. The combination of rotor advance ratios beyond 1.0, large col-lective pitch sweeps, and blade surface pressure measurements makes this data set unique.